Four new species of Heza Amyot & Audinet-Serville (Heteroptera: Reduviidae: Harpactorinae) from the Neotropics - Swanson, Daniel R. (Zootaxa, 2021)
Four new species of the Neotropical harpactorine genus Heza Amyot & Audinet-Serville are newly described: Heza graziae sp. nov. from Ecuador, Heza nebrias sp. nov. from Peru and Brazil, Heza phthinica sp. nov. from Brazil and Peru, and Heza viridipes sp. nov. from Bolivia. Two new country records for two other species are also reported: Heza aurantia Maldonado, 1976 from Ecuador and Heza ventralis Stål, 1872 from Brazil.